1996
DOI: 10.1002/(sici)1097-0193(1996)4:1<23::aid-hbm2>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of PET activation across statistical methods, subject groups, and sample sizes

Abstract: Four pixel-based methods for estimating regional activation in positron emission tomography (PET) images were implemented so as to allow the comparison of their performances in the same dataset. Change distribution analysis, Worsley's method, a pixelwise general linear model, a nonparametric method, and several methods derived from them were investigated. Important technical factors, including the degree of smoothing, stereotactic transform, coregistration algorithm, search volume, and the volumetric alpha lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Specifically, posterior temporal and fusiform activation has been found for other word and object naming tasks [Bookheimer et al, 1995;Howard et al, 1992;Vandenberghe et al, 1996], as well as more complex task conditions. For instance, posterior temporal activation during the verb generation has been reported Grabowski et al, 1996;Warburton et al, 1996], and greater activation in an inferior temporal/ fusiform region was found when subjects judged whether adjective-noun word pairs met a particular semantic constraint (small animals with ''positive'' attributes), than when they judged whether multi-r Fiez r r 80 r syllabic nonwords contained a particular phoneme sequence (/b/ preceded by /d/) [Demonet et al, 1992].…”
Section: How Do the Contributions Of Frontal And Posterior Regions Tomentioning
confidence: 99%
“…Specifically, posterior temporal and fusiform activation has been found for other word and object naming tasks [Bookheimer et al, 1995;Howard et al, 1992;Vandenberghe et al, 1996], as well as more complex task conditions. For instance, posterior temporal activation during the verb generation has been reported Grabowski et al, 1996;Warburton et al, 1996], and greater activation in an inferior temporal/ fusiform region was found when subjects judged whether adjective-noun word pairs met a particular semantic constraint (small animals with ''positive'' attributes), than when they judged whether multi-r Fiez r r 80 r syllabic nonwords contained a particular phoneme sequence (/b/ preceded by /d/) [Demonet et al, 1992].…”
Section: How Do the Contributions Of Frontal And Posterior Regions Tomentioning
confidence: 99%
“…A central problem in brain activation experiments is the reproducibility of the resulting functional activation patterns. To date this issue has been addressed only for spatially localized suprathreshold foci [e.g., Grabowski et al, 1996]. Moreover, comparison of activation patterns using the ''corner-cube environ-ment'' [Schaper et al, 1996] or ''functional volumes models'' [Fox et al, 1996], which provide a symbolic representation of activated foci, typically summarize only spatial information for suprathreshold signals.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous articles on statistical power have thus used repeatability of effects as a criterion for determining the sample size instead of actual power analysis. There are various articles that deal with power in voxel-based functional neuroimaging (Grabowski et al, 1996;Andreasen et al, 1996;Van Horn et al, 1998;Petersson et al, 1999;Desmond and Glover, 2002), but all of them concern activation studies, not PET neuroreceptor studies.…”
Section: Voxel-based Analysis: Powermentioning
confidence: 99%